Mandibular Advancement vs CPAP for Blood Pressure Reduction in Patients with Obstructive Sleep Apnea - Ou, Yi-Hui; Colpani, Juliana Tereza; Cheong, Crystal S; Loke, Weiqiang; Thant, As Tar; Shih, E Ching; Lee, Frank; Chan, Siew-Pang; Sia, Ching-Hui; Koo, Chieh-Yang; Wong, Serene; Chua, Aiping; et al. (Journal of the American College of Cardiology, 2024)
Hypertension guidelines recommend diagnosis and treatment of obstructive sleep apnea (OSA) in patients with hypertension. The mandibular advancement device (MAD) is an oral appliance therapy for patients who decline or cannot tolerate CPAP. We compared the relative effectiveness of MAD versus CPAP in reducing 24-hour ambulatory BP. In an investigator-initiated, randomized, non-inferiority trial (pre-specified margin 1.5 mmHg), 321 participants, aged over 40, with hypertension and increased cardiovascular risk were recruited at 3 public hospitals for polysomnography. Of these, 220 participants with moderate-to-severe OSA (apnea-hypopnea index (AHI) ≥15 events/hour) were randomized to either MAD or CPAP (1:1). The primary outcome was the difference between the 24-hour mean arterial BP at baseline and 6 months. Compared to baseline, the 24-hour mean arterial BP decreased by 2.5 mmHg (P = 0.003) at 6 months in the MAD group, whereas no change was observed in the CPAP group (P = 0.374). The between-group difference was -1.6 mmHg (95% confidence interval: -3.51 to 0.24, non-inferiority P < 0.001). The MAD group demonstrated a larger between-group reduction in all secondary ambulatory BP parameters compared to the CPAP group, with the most pronounced effects observed in the asleep BP parameters. Both the MAD and CPAP improved daytime sleepiness, with the between-group difference similar (P = 0.384). There were no between-group differences in cardiovascular biomarkers. MAD is non-inferior to CPAP for reducing 24-hour mean arterial BP in participants with hypertension and increased cardiovascular risk.